Complex formation in liquid potassium-lead alloy - Singh, BP; Adhikari, D; Jha, IS; Singh, BK (BIBECHANA, 2010)
Regular associated solution model has been used to study the mixing properties of KPb liquid alloy at 848 K. The values of different thermodynamic parameters obtained from this model are compared with corresponding experimental values. Most of the computed values are in good agreement with the observed values. Keywords: Compound forming alloy; Pairwise interaction energy; Equilibrium constant DOI: 10.3126/bibechana.v7i0.4035 BIBECHANA 7 (2011) 1-5